Pendidikan Kesehatan Melalui Media Pembelajaran dalam Pengenalan HIV/AIDS di Kalangan Remaja Produktif - Enni Juliani; Rizqa Wahdini; Yurita Mailintina (Universitas Muhammadiyah Manado, 2024)
HIV/AIDS is a growing global health issue, with an increasing prevalence of cases among adolescents. Adolescents, as a group vulnerable to risky behaviors, require appropriate education on HIV/AIDS prevention. Health education through technology-based learning media, such as social media, educational videos, and other interactive platforms, holds significant potential in improving adolescents' understanding of HIV/AIDS. This study aims to explore the role of learning media in enhancing adolescents' knowledge and awareness about HIV/AIDS. The community service project was conducted at SMAN 76 Jakarta Timur, involving 75 productive-age adolescents. The activity began with a pre-test to assess initial knowledge, followed by an educational session that included a 20-minute video presentation and material discussion, as well as an interactive discussion. After the session, a post-test was administered to measure changes in participants' understanding and awareness levels. The results showed a significant improvement in knowledge about HIV/AIDS and awareness of the importance of prevention. The use of social media as a primary information source also increased, while conventional media such as television and radio saw a decline. These findings suggest that technology-based learning media can be an effective tool in delivering health education. However, attention must be given to the quality of information to avoid the spread of misinformation, and it is crucial to involve medical professionals and reputable institutions in the creation of educational content.